Challenges and Opportunities: EFL Teachers' Teaching Experiences with ICT-Enhanced Professional Development in Higher Education - Kusrini, Endang; Wardani, Niasisca Agustia; Sotlikova, Rimajon (Universitas Pendidikan Mandalika, 2025)
The integration of Information and Communication Technology (ICT) in English as a Foreign Language (EFL) instruction has become increasingly significant in higher education. While ICT offers clear opportunities for enhancing teaching and learning, little research has specifically examined how ICT-enhanced professional development shapes classroom practices in this context. This study aimed to investigate how higher education EFL teachers’ professional development experiences influenced their use of ICT in the classroom and what challenges and opportunities they perceived for their professional growth. A qualitative case study design was employed, involving classroom observations and semi-structured interviews with eight teachers in a university settings. The findings indicate that professional development plays a crucial role in shaping ICT integration, though its impact was uneven across teachers. At the same time, teachers’ experiences revealed a dual reality. While the teachers faced persistent barriers such as limited infrastructure, time constraints, and lack of sustained support, they also recognize clear opportunities for enhancing student engagement, collaboration, and their own professional development. The study underscores the need for institutions to move beyond one-off workshops by developing sustainable, context-sensitive, creating collaborative communities of practice, and embedding continuous mentorship into policy frameworks are critical to bridging the gap between ICT’s potential and its classroom reality. These implications highlight how higher education institutions can design professional development and policy initiatives that not only build teachers’ digital competence but also foster long-term innovation and improved learning outcomes.